Phylogenomic Analysis of Wolbachia Strains Reveals Patterns of Genome Evolution and Recombination. (14th October 2020) - Wang, Xiaozhu; Xiong, Xiao; Cao, Wenqi; Zhang, Chao; Werren, John H; Wang, Xu
Abstract: Wolbachia are widespread intracellular bacteria that mediate many important biological processes in arthropod species. In this study, we identified 210 conserved single-copy genes in 33 genome-sequenced Wolbachia strains in the A–F supergroups. Phylogenomic analyses with these core genes indicate that all 33 Wolbachia strains maintain the supergroup relationship, which was classified previously based on the multilocus sequence typing (MLST) genes. Using an interclade recombination screening method, 14 inter-supergroup recombination events were discovered in six genes (2.9%) among 210 single-copy orthologs. This finding suggests a relatively low frequency of intergroup recombination. Interestingly, they have occurred not only between A and B supergroups (nine events) but also between A and E supergroups (five events). Maintenance of such transfers suggests possible roles in Wolbachia infection-related functions. Comparisons of strain divergence using the five genes of the MLST system show a high correlation (Pearson correlation coefficient r  = 0.98) between MLST and whole-genome divergences, indicating that MLST is a reliable method for identifying related strains when whole-genome data are not available. The phylogenomic analysis and the identified core gene set in our study will serve as a valuable foundation for strain identification and the investigation of recombination and genome evolution in Wolbachia .